Influence of education on responsibility and metabolic control of Type One diabetic patients and parents - Thayebeh Khazaie; Alireza Saadatjoo; Samaneh Noroozi; Fatemeh Moghny; Fahimeh Sadaqany; Fahimeh Alamdar (مجله دانشگاه علوم پزشکی بیرجند, 2014)
Background and Aim: In order to change your lifestyle and improve disease control and responsibility, increased awareness and understanding of the importance of diabetes complications, and treatment is necessary. Target is influence of education on responsibility and metabolic control of Type One diabetic patients and parents. Materials and Methods: In this Quasi-experimental study with purposive sampling, 40 individuals of type1 diabetes and Families were invited and educated and was completed DFRQ: Diabetes Family Responsibility Questionnaire before and 3 months after training. Morning blood glucose and glycosylated hemoglobin were also two times before and after the intervention. Data Analysis with software SPSS version 16.5 with use of statistical ANOVA, test Independent T and couples and Pearson coefficient was done. Results: 40 persons from diabetic patients (62.5%) Female and (37.5%) males with mean age, 14.25 ±6.05 were researched. Mean Morning blood sugar, hemoglobin glycosylated and score patients and parents responsibility before and after Intervention was meaningful difference. Mean responsibility score according to patient age and job father was statistically significant but of sex patient and education was not significant. Between patients and parents responsibility score with the patient age a negative meaningful relationship was obtained. Conclusion: The mean reduction in glycated hemoglobin after training shows poor metabolic control of patients have an acceptable level.